Does training improve users' mental models about adaptive cruise control? - Hungund, Apoorva; Pai, Ganesh; Pradhan, Anuj K. (Traffic Safety Research, 2024)
While Advanced Driver Assistance Systems (ADAS) promise safety benefits to drivers, there is evidence to suggest that drivers are unaware or uninformed about their vehicles’ systems and thus have poor mental models about the systems. Previous studies suggest that training improves drivers’ mental models, although some studies report limited impacts. This study investigated the relationship between training and drivers’ mental models about Adaptive Cruise Control (ACC), compared the impact of two different training approaches on drivers’ mental models, and examined the relationship between driver knowledge and trust regarding ADAS technologies. This study was conducted online, and participants were randomly and equally assigned to one of three training groups – owner’s manual (text-based); state diagram visualization; or sham (control). Surveys measured their trust and mental models about ACC before and after training. The results found that the text-based group outperformed the visualization group and the control group in terms of post-training overall mental model scores, but these differences were not statistically significant. No correlation between post-training mental model scores and overall trust scores was found. This study provides evidence that training improves users’ mental models about technology and finds that different training platforms or paradigms may affect learning differently.